Activity level and aggregation behavior in the crustacean gammarid Gammarus insensibilis parasitized by the manipulative trematode Microphallus papillorobustus - Arnal, Audrey; Droit, Anaïs; Elguero, Eric; Ducasse, Hugo; Sánchez, Marta I.; Lefevre, Thierry; Misse, Dorothée; Bédèrina, Malia; Vittecoq, Marion; Daoust, Simon; Thomas, Frédéric (Frontiers in Ecology and Evolution, 2015)
Hosts manipulated by parasites are profoundly altered organisms exhibiting a broad range of potential modifications. Exploring this multidimensionality is an emerging field. Previous studies have shown that the bird trematode Microphallus papillorobustus induces several behavioural changes in the gammarid Gammarus insensibilis. Knowing that aggregation behaviour and reduced activity levels are strategies that limit predation in other species of amphipods, we explored in this study these behavioural responses for infected and uninfected G. insensibilis in the presence of host and non-host predator olfactory cues (bird faeces and fish mucus). While uninfected individuals reduced their activity level in the presence of predator cues, infected individuals did not change their activity level in presence of aquatic bird faeces. We also studied the gammarid aggregation behaviour. Uninfected gammarids in clean water spent significantly more time in aggregates than did infected individuals. Among the uninfected individuals, the aggregation level tended to increase when bird faeces and fish mucus were added, but the difference was not significant. Among infected individuals, the level of aggregation was significantly increased only with the bird faeces. We discussed our results in the context of the literature on multidimensional manipulations, acknowledging that subtle differences between unparasitized and parasitized gammarids can also be by-products of manipulation on other traits.